2017
DOI: 10.1038/s41559-017-0109
|View full text |Cite
|
Sign up to set email alerts
|

Community structure follows simple assembly rules in microbial microcosms

Abstract: Microorganisms typically form diverse communities of interacting species, whose activities have tremendous impact on the plants, animals and humans they associate with. The ability to predict the structure of these complex communities is crucial to understanding and managing them. Here, we propose a simple, qualitative assembly rule that predicts community structure from the outcomes of competitions between small sets of species, and experimentally assess its predictive power using synthetic microbial communit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
594
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(672 citation statements)
references
References 33 publications
29
594
6
1
Order By: Relevance
“…Our results contrast with other studies that have found fully hierarchical competition (e.g. Grace et al., in vascular plants; Henriksson et al., in fishes; Friedman, Higgins, & Gore, in bacteria). The variety of methods used to measure competition may contribute to this lack of consensus.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results contrast with other studies that have found fully hierarchical competition (e.g. Grace et al., in vascular plants; Henriksson et al., in fishes; Friedman, Higgins, & Gore, in bacteria). The variety of methods used to measure competition may contribute to this lack of consensus.…”
Section: Discussioncontrasting
confidence: 99%
“…Three‐species experiments (Kerr et al., ) and mathematical models (Laird & Schamp, ; Reichenbach et al., ; Yitbarek & Vandermeer, ) suggest that intransitive competition is less frequent in mobile taxa that compete in “global” neighbourhoods as opposed to those that compete locally (sessile organisms). This is supported by the lack of intransitive competition found in other manipulative experiments with organisms growing in well‐mixed environments, such as bacteria (Friedman et al., ), aquatic protists (Vandermeer, ), or necrophagous insects (Ulrich et al., ). Despite this, we found no strong evidence for a reduction in intransitivity in mobile taxa, mainly due to the high level observed in protists (but see Carrara et al., ) and the moderate levels found in fungi.…”
Section: Discussionmentioning
confidence: 83%
“…Our results substantiate the notion that monospecies growth parameters and pairwise interactions dominate multi‐species community dynamics (Friedman et al , ). It is possible that higher‐order interactions significantly influence community dynamics in lower dimensional multi‐species assemblages, such as three‐member consortia.…”
Section: Discussionsupporting
confidence: 90%
“…For example, an L-V pairwise model and a mechanistic model both correctly predicted ratio stabilization and spatial intermixing between two strongly-cooperating populations exchanging diffusible essential metabolites (Momeni et al, 2013). In other examples, pairwise models largely captured competition outcomes and metabolic activities of three-species and four-species artificial microbial communities (Vandermeer, 1969; Guo and Boedicker, 2016; Friedman et al, 2017). On the other hand, pairwise models often failed to predict species coexistence in seven-species microbial communities (Friedman et al, 2017), although this could be due to interaction modification discussed above.
10.7554/eLife.25051.006Figure 2.Chemical-mediated interactions commonly found in microbial communities.Interactions can be intra- or inter-population.
…”
Section: Introductionmentioning
confidence: 99%
“…In other examples, pairwise models largely captured competition outcomes and metabolic activities of three-species and four-species artificial microbial communities (Vandermeer, 1969; Guo and Boedicker, 2016; Friedman et al, 2017). On the other hand, pairwise models often failed to predict species coexistence in seven-species microbial communities (Friedman et al, 2017), although this could be due to interaction modification discussed above.
10.7554/eLife.25051.006Figure 2.Chemical-mediated interactions commonly found in microbial communities.Interactions can be intra- or inter-population. Examples are meant to be illustrative instead of comprehensive. DOI: http://dx.doi.org/10.7554/eLife.25051.006
…”
Section: Introductionmentioning
confidence: 99%